2007
DOI: 10.1088/1367-2630/9/5/133
|View full text |Cite
|
Sign up to set email alerts
|

Ultracold atomic Bose and Fermi spinor gases in optical lattices

Abstract: We investigate magnetic properties of Mott-insulating phases of ultracold Bose and Fermi spinor gases in optical lattices. We consider in particular the F = 2 Bose gas, and the F = 3/2 and F = 5/2 Fermi gases. We derive effective spin Hamiltonians for one and two atoms per site and discuss the possibilities of manipulating the magnetic properties of the system using optical Feshbach resonances. We discuss low temperature quantum phases of a 87 Rb gas in the F = 2 hyperfine state, as well as possible realizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 95 publications
1
28
0
Order By: Relevance
“…Such superexchange interactions are believed to play an important role in the context of high-T c superconductivity (9). Furthermore, they can form the basis for the generation of robust quantum gates similar to recent work in electronic double quantum dot systems (10, 11), and can be used for the efficient generation of multi-particle entangled states (12, 13), as well as for the production of many-body quantum phases with topological order (14,15,16).We report on the direct observation of superexchange interactions with ultracold atoms in optical lattices (17,18). Previous experiments have shown that spin-spin interactions between neighboring atoms can be implemented in discrete time steps (19,20) by bringing the atoms together on a single site and carrying out controlled collisions (21,20,22) or onsite exchange interactions (23).…”
mentioning
confidence: 83%
“…Such superexchange interactions are believed to play an important role in the context of high-T c superconductivity (9). Furthermore, they can form the basis for the generation of robust quantum gates similar to recent work in electronic double quantum dot systems (10, 11), and can be used for the efficient generation of multi-particle entangled states (12, 13), as well as for the production of many-body quantum phases with topological order (14,15,16).We report on the direct observation of superexchange interactions with ultracold atoms in optical lattices (17,18). Previous experiments have shown that spin-spin interactions between neighboring atoms can be implemented in discrete time steps (19,20) by bringing the atoms together on a single site and carrying out controlled collisions (21,20,22) or onsite exchange interactions (23).…”
mentioning
confidence: 83%
“…In this work, different families of multicolor bright spatial optical solitons were found by numerical integration of the corresponding stationary equations only. Cases 3 and 4 also emerge in the context of fermionic condensates of ultracold atoms [27][28][29][30], although there are some difficulties in both the justification of mean-field condensate wave function for fermions as well as possible pairing instabilities of superconducting types. Nevertheless, with sufficient care, our cases 3 and 4 can model four-component spin-3/2 cold atomic systems under special circumstances.…”
Section: Casementioning
confidence: 99%
“…[11][12][13]). In this case, in principle, the number of (relevant) components can be controlled (from 2 to 2F + 1) using optical methods, and Feshbach resonances may be used to tune the desired collisional channels.…”
Section: Introductionmentioning
confidence: 99%